Advanced LIF-ZNS(AG) thermal neutron detector; International Congress on Energy Fluxes and Radiation Effects (EFRE-2014), September 21–26, 2014, Tomsk, Russia - Dubtsov I. N. Igor Nikolaevich; Andryushenko L. A. Lyudmila Aleksandrovna; Tarasov V. P. Vadim Petrovich; Shpilinskaya O. V. Olga Viktorovna; Trefilova L. N. Larisa Nikolaevna; Yakovlev V. Yu. Viktor Yurjevich; Lisitsyn V. M. Viktor Mikhailovich; Dudnik A. V. Anna Vladimirovna (2014, 2014)
Title screen